The Quality of University Education at the Middle Technical University in The Light of the Application of National Ranking project for the Quality of Iraqi Universities - عبد فريد مجيد; محمد الجاف نادية عبد الله (Journal of Economics and Administrative Sciences, 2025)
The research aims to identify ways of upgrading the quality level of university education at the Middle Technical University in light of its application for the National Ranking project for the quality of Iraqi universities in order to obtain advanced grades among the Iraqi universities , Which is qualified to enter the Ranking of universities worldwide, through displaying the mechanism of the Application of National Ranking project for the quality of Iraqi universities in the Middle Technical University and its formations consisting of (5) technical colleges and (11) technical institute. The results of the application showed several observations: The most significant of which are the accredited standards did not take into account the existence of two levels of study at the Middle Technical University (technical diploma and technical bachelor) compared to other Iraqi universities that are restricted to one level that is the bachelor, which negatively affected the degree of university evaluation. The research, through adopting the descriptive approach, reached a set of recommendations and proposals necessary for upgrading the university and promoting its quality, the most important of which is the reconsideration of the objective standards in such a way that suits the technical education which differs from academic education in its adoption on the applied practical side greatly. The research also stressed on the necessity of boosting academic cooperation relationships between the Middle Technical University and its counterparts of Iraqi and Arab universities to define joint issues from different perspectives and benefit from successful experiences in developing work to upgrade the quality of technical education.